Who participates in 'participatory design' of WASH infrastructure: A mixed-methods process evaluation. - Thea L Mink; Allison P Salinger; Naomi Francis; Becky Batagol; Kerrie Burge; Noor Ilhamsyah; Losalini Malumu; Liza Marzaman; Michaela F Prescott; Nur Intan Putri; Sheela S Sinharoy (PLOS Global Public Health)
Inclusive participation is critical for community-based water, sanitation and hygiene (WASH) interventions, especially in complex environments such as urban informal settlements. We conducted a mixed-methods, theory-driven process evaluation to evaluate participation, barriers to participation, and participant satisfaction within the Revitalising Informal Settlements and their Environments (RISE) trial in Makassar, Indonesia and Suva, Fiji (ACTRN12618000633280; https://www.anzctr.org.au/). RISE conducted participatory design activities, including community-level design workshops and household visits, to co-design WASH infrastructure. Household surveys, conducted with women and men after RISE participatory design in Makassar (N = 320) and Suva (N = 503), captured self-reported participation in RISE activities and satisfaction with influence over RISE decision-making. We used logistic regression models to assess socio-demographic predictors of participation and satisfaction. Qualitative data were also collected after participatory design and analyzed thematically. Most respondents from Makassar (89%) and Suva (75%) participated in at least one RISE activity. Statistically significant predictors of participation included gender, age, and marital status in Makassar and disability status and education in Suva. Most participants in Makassar (66%) and Suva (70%) were satisfied with their level of influence over RISE decision-making. In Makassar, no significant predictors of satisfaction were identified. In Suva, significant predictors of satisfaction included gender, religion, and marital status, with women wanting more influence and religious minorities and unmarried participants wanting less influence over decisions. Qualitative data showed that most participants felt satisfied by RISE's inclusive and participatory design, although some residents reported distrust with RISE and feeling excluded from activities by community representatives. While RISE participatory design activities achieved good reach and satisfaction overall, we identified specific gender and social inequities in participation and influence over decision-making. We recommend that WASH interventions reflect on the quality of their engagement with communities and local organizations in order to identify and appropriately include groups of interest.